An asymmetric synthesis of all stereoisomers of piclavines A1-4 using an iterative asymmetric dihydroxylation - Saito, Yukako; Okamoto, Naoki; Takahata, Hiroki (Beilstein Journal of Organic Chemistry, 2007)
The asymmetric synthesis of both enantiomers of piclavines A1, A2, A3, and A4 has been achieved using an iterative asymmetric dihydroxylation with enantiomeric enhancement.